Seedling Production of Retrophyllum rospigliosii in Nurseries and Potential Reforestation Areas Using Modeling Techniques - Camarena Yupanqui, Rozly Clarita; Orellana Mendoza, Edith; Bernaola Paucar, Rosario Marilu; Ames Martínez, Fressia Nathalie; Loardo Tovar, Harold; Quispe Melgar, Harold Rusbelth (MDPI, 2025)
The success of reforestation and restoration projects depends on several factors, with proper seedling management and the selection of an appropriate planting area being crucial. In Peru, the populations of Retrophyllum rospigliosii (Pilg.) C.N.Page (Ulcumano) have been decreasing due to intensive logging of one of the most valuable woods in South America's tropical forests. There are few studies that unify the production of plants through seeds in nurseries and the identification of suitable areas to place the plants produced. Our study has two components. The first aimed to optimize the plant production process through an experiment that evaluated the effects of three doses of controlled-release fertilizer (CRF) (4.2, 8.4, and 12.6 g/L) and two container sizes (115 and 180 cc) on the morphological quality of seedlings in the nursery. The second component involved identifying potential reforestation areas using ecological niche modeling, based on climatic and edaphic variables. The results indicated that the 4.2 g/L CRF treatment for both container sizes had a significant positive effect on seedling growth. The average germination rate was 85% at 120 days. At six months after seedling transplantation, treatments of 4.2 g/L CRF in 115 cc and 180 cc containers were shown to have the best positive effect on morphological variables of seedlings, with a root collar diameter of 3.76 mm and a height of 13.25 cm. Regarding the potential niche models, an area of 6321.97 km² with ideal conditions for reforestation with R. rospigliosii was estimated, with the departments of Huánuco, Pasco, Junín, and Cusco showing the highest potential. Based on this, it is estimated that over three million plants are needed for large-scale reforestation projects. Integrating silvicultural studies with niche models is a valuable tool for supporting reforestation and ecosystem restoration projects.